An IoT-Based System for Monitoring Electricity Usage in Student Dorm Rooms Using the ESP32 - muhammad syaifuddin; Zainal Abidin; Rifky Aisyatul Faroh (Universitas Sangga Buana, 2026)
Real-time monitoring and control of electrical energy usage is essential in effective power consumption management, especially in environments such as boarding houses or rental rooms. This study designs and implements an Internet of Things (IoT)-based system using the ESP32 microcontroller integrated with the PZEM-004T sensor, relay module, and OLED display. The ESP32 is selected for its built-in WiFi connectivity and efficient data processing capabilities. The PZEM-004T sensor is used to measure electrical parameters such as voltage, current, power, and energy (kWh). The relay module functions as an electronic switch that controls the flow of electricity to appliances either automatically or manually via the Blynk application. Meanwhile, the OLED screen locally displays energy consumption information for each room. The system is capable of independently monitoring and displaying power usage per room while also estimating electricity costs based on a predefined kWh tariff. With the help of the Blynk app, users can remotely access real-time data and control electrical devices as needed. Each room is equipped with one sensor, one relay, and one OLED display, all connected to a single ESP32 unit, allowing efficient multi-point monitoring. Testing results indicate that the system performs accurately and responsively. This implementation is expected to help boarding house residents better manage their energy usage, promote awareness of energy efficiency, and reduce unnecessary electricity expenses.